E Etnomedicine Tumbuhan Obat di Masyarakat Desa Belangian, Kalimantan Selatan: - Syahfitri, Laili Shinta Ayu; Nastiti, Kunti; Kurniawati, Darini; Rohama, Rohama (LPPM Universitas Sari Mulia, 2024)
Background: The diversity of tribes and cultures in Indonesia makes culturaldifferences and traditional knowledge, one of which is in utilizing plants for thetreatment of a disease. One of the widespread tribes on the island of Kalimantanthat is thick with traditional medicine is the Banjar Tribe located in BelangianVillage, South Kalimantan. Ethnomedisin is a treatment by certain ethnicities basedon hereditary traditions in traditional medicine, in this case the use of medicinalplants.Objective: The purpose of this study was to determine the ethnomedicine ofmedicinal plants used by the Banjar Tribe of Belangian Village, Aranio District,South Kalimantan Province.Methods: This research is descriptive using qualitative and quantitative methods.Quantitative analysis with Fidelity Level (FL) calculations for each type ofmedicinal plant.Result: Based on the results of research from 38 informants, 58 species with 36families were obtained. There are 50 diseases that can be treated from 58 types ofmedicinal plants. The most popular method of processing is boiled 56.89 then drunk72.41%. The most widely used part of medicinal plants is the leaf part of 41.73%.Five types of plants with the highest FL values that stated effectiveness for treatmentwere Cymbopogon citratus 86.84%, Zingiber officinale 78.94%, Jatropha multifidaL 73.64%, Peronema canescens jack 68.42%, Syzygium polyanthum 65.78%. Thetradition of treatment with medicinal plants by the Banjar Tribe has been passeddown for generations with the value of local wisdom in its use.Conclusion: There are 58 types of medicinal plants that can be used as medicineor relief for certain diseases by the people of the Banjar Tribe, Belangian Village.With the highest FL value of five is found in Cymbopogon citratus plants 86.84%,Zingiber officinale 78.94%, Jatropha multifida L 73.64%, Peronema canescensjack 68.42%, Syzygium polyanthum 65.78%.